Sustainable agriculture impacts in urban settings make the case for federal investments - Hagan Capnerhurst; Hannah Quigley; Jason Hawes (Journal of Agriculture, Food Systems, and Community Development)
Urban agriculture has flourished in American cities under the care of communities, but its growing popularity faces a number of challenges related to scant funding, insecure land tenure, and environmental pollution. Both local and national policy in the U.S. have struggled to adequately address those challenges and meet the demand for fresh food, local production spaces, and resilient communities. In this policy brief, we explore an emerging apparatus to support urban agriculture in the U.S. Department of Agriculture: The Office of Urban Agriculture and Innovative Production. We describe the relationship between urban agriculture’s many benefits and future funding, technical assistance, and data collection initiatives through this office. Specifically, we call for consistent, permanent funding that is not subject to the annual federal budget process, which could power more tailored technical assistance programs, reformed granting initiatives, and expanded data collection to inform future policy and practice. Urban agriculture has the potential to transform communities and the future of farming, and federal policy has the potential to provide important support for this transformation. The policies outlined here offer a roadmap for this support.